Mangifera indica L. Leaf Extract in Combination With Luteolin or Quercetin Enhances VO2peak and Peak Power Output, and Preserves Skeletal Muscle Function During Ischemia-Reperfusion in Humans - Gelabert-Rebato, Miriam; Wiebe, Julia C.; Martin-Rincon, Marcos; Gericke, Nigel; Perez-Valera, Mario; Curtelin, David; Galvan-Alvarez, Victor; Lopez-Rios, Laura; Morales-Alamo, David; Calbet, Jose A. L. (Frontiers in Physiology, 2018)
It remains unknown whether polyphenols such as luteolin (Lut), mangiferin and quercetin (Q) have ergogenic effects during repeated all-out prolonged sprints. Here we tested the effect of Mangifera indica L. leaf extract (MLE) rich in mangiferin (Zynamite®) administered with either quercetin (Q) and tiger nut extract (TNE), or with luteolin (Lut) on sprint performance and recovery from ischemia-reperfusion. Thirty young volunteers were randomly assigned to three treatments 48h before exercise. Treatment A: placebo (500 mg of maltodextrin/day); B: 140 mg of MLE (60% mangiferin) and 50 mg of Lut/day; and C: 140 mg of MLE, 600 mg of Q and 350 mg of TNE/day. After warm-up, subjects performed two 30s Wingate tests and a 60s all-out sprint interspaced by 4-min recovery periods. At the end of the 60-s sprint the circulation of both legs was instantaneously occluded for 20s. Then, the circulation was re-opened and a 15-s sprint performed, followed by 10 s recovery with open circulation, and another 15-s final sprint. MLE supplements enhanced peak (Wpeak) and mean (Wmean) power output by 5.0-7.0% (P<0.01). After ischemia, MLE+Q+TNE increased Wpeak by 19.4 and 10.2% compared with the placebo (P<0.001) and MLE+Lut (P<0.05), respectively. MLE+Q+TNE increased Wmean post-ischemia by 11.2 and 6.7% compared with the placebo (P<0.001) and MLE+Lut (P=0.012). Mean VO2 during the sprints was unchanged, suggesting increased efficiency or recruitment of the anaerobic capacity after MLE ingestion. In women, peak VO2 during the repeated sprints was 5.8% greater after the administration of MLE, coinciding with better brain oxygenation. MLE attenuated the metaboreflex hyperpneic response post-ischemia, may have improved O2 extraction by the vastus lateralis (MLE+Q+TNE vs placebo, P=0.056), and reduced pain during ischemia (P=0.068). Blood lactate, acid-base balance and plasma electrolytes responses were not altered by the supplements. In conclusion, a MLE extract rich in mangiferin combined with either quercetin and tiger nut extract or luteolin exerts a remarkable ergogenic effect, increasing muscle power in fatigued subjects and enhancing peak VO2 and brain oxygenation in women during prolonged sprinting. Importantly, the combination of MLE+Q+TNE improves skeletal muscle contractile function during ischemia/reperfusion.